PENDIDIKAN KESEHATAN KEPADA IBU NIFAS TENTANG CARA MEMANDIKAN BAYI DAN PERAWATAN TALI PUSAT - Eva Silviana; Umu Qonitun; PS Dwi Kurnia; Faridatul F Lilia (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2020)
Background: The 15th Midwifery Service Standard states that the Midwife provide services during the postpartum period through home visits. Most Midwives Private Practices (BPS) in the Tuban area have made at least 3 home visits times during the puerperium. In the care of newborns, almost 80% of postpartum mothers do not bathe the baby herself but the midwife bathes her until the umbilical cord falls off with the reason that the mother has not dared to bathe her baby for fear of the umbilical cord still wet, the baby is still too small and the mother's lack of knowledge in bathe the baby. The purpose of doing this community service is so that postpartum mothers understand how to care for newborns and are able to independently bathe the baby and care for the umbilical cord properly. Method: In This community service uses a pre-experimental type (Static-group comparison designs). The population of all postpartum mothers is 33 people. Taking sample by consecutive sampling. The sample size is 24 people, namely 12 people the treatment group and 12 people in the control group. The test used is Test MC Nemar has a Chi Square distribution (c 2 ). Result: The results obtained a change that significant difference between before and after being given health education in the group treatment, namely c2 count (4.50) is greater than table c2 (3.481) then HI is rejected,which shows that there is an influence between the provision of education, how early neonate bathing and how to care for the umbilical cord in postpartum mothers. Conclusion: The attitude of the postpartum mother in bathing the baby and caring for the umbilical cord can be affected by providing health education. Midwives are expected in postpartum visits too teach postpartum mothers about how to bathe babies and care for the umbilical cord.